MONITORING TRANSPARENCY AND ACCOUNTABILITY IN PUBLIC GOVERNANCE - Devi Yulianti; Syarief Makhya; Fitri Juliana Sanjaya (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This study examines how transparency and accountability are monitored within public governance through the implementation of the Regional and Financial Information Management System at the Financial and Asset Management Agency of Metro City, Lampung Province, Indonesia. Although the financial system information was nationally introduced in 2007 to modernize financial administration, its practical application has revealed persistent institutional and human resources challenges. Adopting a qualitative research design with a single case study approach, the analysis applies Yin's theory-driven strategy to compare empirical findings with normative expectations grounded in good governance, public administration, human resource management, and digital governance. Data were gathered through direct observations, document reviews, and in-depth interviews with key administrative personnel. The study addresses two main research questions: how the financial system supports transparency and accountability in local financial processes, and how human resource development contributes to its effectiveness. Findings indicate that while the system provided structural support for compliance and reporting, its function as a tool for active governance remains constrained by limited capacity building, fragmented procedures, and weak institutional alignment. The study concludes that digital tools alone are insufficient without a strong institutional culture and human competence. Recommendations include structured training programs, standardized procedures, and real-time monitoring mechanisms to reinforce the financial system information in public accountability.